Operative versus non-operative treatment for 2-part proximal humerus fracture: A multicenter randomized controlled trial - Launonen, Antti P.; Sumrein, Bakir O.; Reito, Aleksi; Lepola, Vesa; Paloneva, Juha; Jonsson, Kenneth B.; Wolf, Olof; Ström, Peter; Berg, Hans E.; Felländer-Tsai, Li; Jansson, Karl-Åke; Fell, Daniel; et al. (PLoS medicine, 2019)
Although increasingly used, the benefit of surgical treatment of displaced 2-part proximal humerus fractures has not been proven. This trial evaluates the clinical effectiveness of surgery with locking plate compared with non-operative treatment for these fractures. The NITEP group conducted a superiority, assessor-blinded, multicenter randomized trial in 6 hospitals in Finland, Estonia, Sweden, and Denmark. Eighty-eight patients aged 60 years or older with displaced (more than 1 cm or 45 degrees) 2-part surgical or anatomical neck proximal humerus fracture were randomly assigned in a 1:1 ratio to undergo either operative treatment with a locking plate or non-operative treatment. The mean age of patients was 72 years in the non-operative group and 73 years in the operative group, with a female sex distribution of 95% and 87%, respectively. Patients were recruited between February 2011 and April 2016. The primary outcome measure was Disabilities of Arm, Shoulder, and Hand (DASH) score at 2-year follow-up. Secondary outcomes included Constant-Murley score, the visual analogue scale for pain, the quality of life questionnaire 15D, EuroQol Group's 5-dimension self-reported questionnaire EQ-5D, the Oxford Shoulder Score, and complications. The mean DASH score (0 best, 100 worst) at 2 years was 18.5 points for the operative treatment group and 17.4 points for the non-operative group (mean difference 1.1 [95% CI -7.8 to 9.4], p = 0.81). At 2 years, there were no statistically or clinically significant between-group differences in any of the outcome measures. All 3 complications resulting in secondary surgery occurred in the operative group. The lack of blinding in patient-reported outcome assessment is a limitation of the study. Our assessor physiotherapists were, however, blinded. This trial found no significant difference in clinical outcomes at 2 years between surgery and non-operative treatment in patients 60 years of age or older with displaced 2-part fractures of the proximal humerus. These results suggest that the current practice of performing surgery on the majority of displaced proximal 2-part fractures of the humerus in older adults may not be beneficial. ClinicalTrials.gov NCT01246167.